9x+4=7-(5x-6)

Simple and best practice solution for 9x+4=7-(5x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+4=7-(5x-6) equation:


Simplifying
9x + 4 = 7 + -1(5x + -6)

Reorder the terms:
4 + 9x = 7 + -1(5x + -6)

Reorder the terms:
4 + 9x = 7 + -1(-6 + 5x)
4 + 9x = 7 + (-6 * -1 + 5x * -1)
4 + 9x = 7 + (6 + -5x)

Combine like terms: 7 + 6 = 13
4 + 9x = 13 + -5x

Solving
4 + 9x = 13 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
4 + 9x + 5x = 13 + -5x + 5x

Combine like terms: 9x + 5x = 14x
4 + 14x = 13 + -5x + 5x

Combine like terms: -5x + 5x = 0
4 + 14x = 13 + 0
4 + 14x = 13

Add '-4' to each side of the equation.
4 + -4 + 14x = 13 + -4

Combine like terms: 4 + -4 = 0
0 + 14x = 13 + -4
14x = 13 + -4

Combine like terms: 13 + -4 = 9
14x = 9

Divide each side by '14'.
x = 0.6428571429

Simplifying
x = 0.6428571429

See similar equations:

| -9(1x-12)=-1x+68 | | lny=x+c | | 2(x-5)=3x+9 | | 5+35x=28x+11 | | X-3-5=7x | | 5(a-3)=95 | | 4x+16=x-35 | | x^2=8x+33 | | (u+2)*9=27 | | cosx-3sinx=0 | | 3x+7=x-16 | | 20x+16=6x-18 | | 5+78x=39x+23 | | 2x+8=-26 | | 49-2x=14-7x | | 7x-4=3x-24 | | 2(-4+5)+7= | | 5.8x=-27.84 | | 7h+4=74 | | 20=5(x-3) | | 52=130 | | -4.3x-3.2= | | 3(n-2)-n=10 | | 3x+7=-47-6x | | 6x+5=2x+15 | | 4x-10=3x+7 | | -5.7= | | 1+8x=1+x | | 4f-7=12 | | -3x+5y=0 | | b^2+a-a^2+i(-b-2ab)=0 | | 5(a+3b)-3(a-b)= |

Equations solver categories